Effects of a self-affirmation intervention among Chinese adolescents during the COVID-19 pandemic: A large-scale randomized controlled trial - Wei Yan; Wang, Yuling; Jiang, Zhongxin; Peng, Kaiping; Cohen, Geoffrey (Applied Psychology: Health and Well‐Being, 2024)
The COVID-19 pandemic, characterized by its highly contagious nature and devastating death toll, posed a dual threat to both physical and psychological well-being. As a potential intervention to alleviate the psychological impact, values-affirmation involves individuals engaging in the activity of writing about their core values. While its effectiveness in non-WEIRD (i.e. Western, Educated, Industrialized, Rich, Democratic) populations, notably among Chinese adults, has been confirmed, it remains largely unexplored whether the intervention can promote mental health in Chinese adolescents, especially in the context of the COVID-19 pandemic. The purpose of this study thus is to provide the first empirical evaluation of this intervention in promoting well-being and alleviating psychological distress among Chinese adolescents during the COVID-19 pandemic. A total of 2,234 students from 112 secondary schools in China were randomly assigned to an affirmation or control condition. The study found that self-affirmation intervention improved students' life satisfaction, mental health, and self-esteem, as well as buffered a decline of their purpose in life; however, no effects were found for clinical measures of depression, anxiety, and loneliness. The results suggest that self-affirmation interventions, while having limited effects on clinically relevant outcomes, can be an effective approach to boost well-being in adolescents during a major crisis, including in a more historically collectivist culture. Implications for self-affirmation theory and cultural psychology, as well as avenues for future research, are discussed.